Why do some women still prefer traditional birth attendants and home delivery?: a qualitative study on delivery care services in West Java Province, Indonesia - Titaley Christiana R; Hunter Cynthia L; Dibley Michael J; Heywood Peter (BMC, 2010)
Abstract Background Trained birth attendants at delivery are important for preventing both maternal and newborn deaths. West Java is one of the provinces on Java Island, Indonesia, where many women still deliver at home and without the assistance of trained birth attendants. This study aims to explore the perspectives of community members and health workers about the use of delivery care services in six villages of West Java Province. Methods A qualitative study using focus group discussions (FGDs) and in-depth interviews was conducted in six villages of three districts in West Java Province from March to July 2009. Twenty FGDs and 165 in-depth interviews were conducted involving a total of 295 participants representing mothers, fathers, health care providers, traditional birth attendants and community leaders. The FGD and in-depth interview guidelines included reasons for using a trained or a traditional birth attendant and reasons for having a home or an institutional delivery. Results The use of traditional birth attendants and home delivery were preferable for some community members despite the availability of the village midwife in the village. Physical distance and financial limitations were two major constraints that prevented community members from accessing and using trained attendants and institutional deliveries. A number of respondents reported that trained delivery attendants or an institutional delivery were only aimed at women who experienced obstetric complications. The limited availability of health care providers was reported by residents in remote areas. In these settings the village midwife, who was sometimes the only health care provider, frequently travelled out of the village. The community perceived the role of both village midwives and traditional birth attendants as essential for providing maternal and health care services. Conclusions A comprehensive strategy to increase the availability, accessibility, and affordability of delivery care services should be considered in these West Java areas. Health education strategies are required to increase community awareness about the importance of health services along with the existing financing mechanisms for the poor communities. Public health strategies involving traditional birth attendants will be beneficial particularly in remote areas where their services are highly utilized.